Iracema Oliveira: Mestra da Cultura e do Teatro Popular no Pará - JORGE, Sâmela Cristina de Souza (Universidade Federal do Pará, 2024)
This research investigated the trajectory of the Master of Popular Culture Iracema Oliveira and the sociocultural meanings of her work with the popular artistic movement in the city of Belém do Pará. Guardian of the Bird Junino Tucano, coordinator of Pastorinha Filhas de Sion and the parafolkloric group Frutos do Pará, Iracema Oliveira presents his own methodology for transmitting knowledge, an organization of artistic processes that contribute to the understanding of popular culture as a dynamic process, built over time and crossed by politics and social changes. Methodologically, we make use of participant observation (Minayo, 2001; Whyte, 2005) and documentary research, moving between epistemologies about art, music, theater, popular culture, Amazonian cultural history, to debate identity, memory and local culture from the research phenomenon, based n questions raised by Joël Candau (2012), Stuart Hall (2006), Bezerra (2016), Fares and Rodrigues (2017) among others. As a result, we hope that the research will contribute with new perspectives on the popular art system in Pará, based on the trajectory of Master Iracema Oliveira, bringing together a potential collection of memories, which tell about her experiences of art and life, and the sociocultural meanings of popular artistic practices in the capital of Pará, historically sown and maintained in the present time by the collective desire to make, sing and dance traditions.